Air oxidation of sulfur mustard gas simulants using a pyrene-based metal–organic framework photocatalyst - Ayoub, Ghada; Arhangelskis, Mihails; Zhang, Xuan; Son, Florencia; Islamoglu, Timur; Friščić, Tomislav; Farha, Omar K. (Beilstein Journal of Nanotechnology, 2019)
We demonstrate a microporous metal–organic framework NU-400 based on a 2,7-disubstituted pyrene linker as a highly efficient photosensitizer for generating singlet oxygen and subsequent oxidative degradation of chemical warfare agents (CWAs). The high activity of NU-400 permits photocatalytic conversion of the 2-chloroethyl ethyl sulfide (CEES) mustard gas simulant into a benign sulfoxide derivative, in air, with less than 15 minutes’ half-life. This is a considerable improvement to NU-1000, based on a 1,3,6,8-tetrasubstituted pyrene unit, demonstrating how variation of the substitution pattern of a metal–organic framework linker permits modification of its photoactive behavior.
Keywords: metal-organic frameworks; oxidation; photocatalysis; singlet oxygen; sulfur mustard gas

(untitled) - Fitzgerald, G. J. (Am. J. Public Health, 2008)

(untitled) - Sidell, F. R.; Borak, J. (Ann. Emerg. Med., 1992)

Organisation for the Prohibition of Chemical Weapons. Chemical Weapons Convention

UN says Syria and Islamic State used chemical weapons, Chemical and Engineering News, August 2016 - Hess, G.
https://cen.acs.org/articles/94/web/2016/08/UN-says-Syria-Islamic-State.html

Report Finds Chemical Weapons Used by Syrian Regime, Islamic State - Fassihi, F. U. N. (The Wall Street Journal, 2016)

(untitled) - Sezigen, S.; Eyison, R. K.; Kenar, L. (Gulhane Med. J., 2019)

(untitled) - Irvine, D. A.; Earley, J. P.; Cassidy, D. P.; Harvey, S. P. (Water Sci. Technol., 1997)

(untitled) - Wang, Q.-Q.; Begum, R. A.; Day, V. W.; Bowman-James, K. (Org. Biomol. Chem., 2012)

(untitled) - Wagner, G. W.; Bartram, P. W.; Koper, O.; Klabunde, K. J. (J. Phys. Chem. B, 1999)

(untitled) - Wagner, G. W.; Koper, O. B.; Lucas, E.; Decker, S.; Klabunde, K. J. (J. Phys. Chem. B, 2000)

(untitled) - Horcajada, P.; Surblé, S.; Serre, C.; Hong, D.-Y.; Seo, Y.-K.; Chang, J.-S.; Grenèche, J.-M.; Margiolaki, I.; Férey, G. (Chem. Commun., 2007)

(untitled) - Popiel, S.; Nawała, J. (Enzyme Microb. Technol., 2013)

(untitled) - Price, C. C.; Bullitt, O. H. (J. Org. Chem., 1947)

(untitled) - Gall, R. D.; Faraj, M.; Hill, C. L. (Inorg. Chem., 1994)

(untitled) - Richardson, D. E.; Yao, H.; Frank, K. M.; Bennett, D. A. (J. Am. Chem. Soc., 2000)

(untitled) - Boring, E.; Geletii, Y. V.; Hill, C. L. (J. Am. Chem. Soc., 2001)

(untitled) - Ringenbach, C. R.; Livingston, S. R.; Kumar, D.; Landry, C. C. (Chem. Mater., 2005)

(untitled) - Wagner, G. W.; Yang, Y.-C. (Ind. Eng. Chem. Res., 2002)

(untitled) - Hirade, J.; Ninomiya, A. (J. Biochem., 1950)

(untitled) - Yang, Y. C.; Baker, J. A.; Ward, J. R. (Chem. Rev., 1992)

(untitled) - Jang, Y. J.; Kim, K.; Tsay, O. G.; Atwood, D. A.; Churchill, D. G. (Chem. Rev., 2015)

(untitled) - DeRosa, M. C.; Crutchley, R. J. (Coord. Chem. Rev., 2002)

(untitled) - Griesbeck, A. G.; El-Idreesy, T. T.; Bartoschek, A. (Adv. Synth. Catal., 2004)

Singlet Oxygen: Applications in Biosciences and Nanosciences - Roman, E. S. (Heterogeneous Singlet Oxygen Sensitizers, 2016)

(untitled) - Li, H.; Eddaoudi, M.; O'Keeffe, M.; Yaghi, O. M. (Nature, 1999)

(untitled) - Férey, G. (Chem. Soc. Rev., 2008)

(untitled) - Cooper, A. I.; Rosseinsky, M. J. (Nat. Chem., 2009)

(untitled) - Shimizu, G. K. H.; Vaidhyanathan, R.; Taylor, J. M. (Chem. Soc. Rev., 2009)

(untitled) - Zhou, H.-C.; Long, J. R.; Yaghi, O. M. (Chem. Rev., 2012)

(untitled) - Chen, Z.; Hanna, S. L.; Redfern, L. R.; Alezi, D.; Islamoglu, T.; Farha, O. K. (Coord. Chem. Rev., 2019)

(untitled) - Denny, M. S., Jr; Moreton, J. C.; Benz, L.; Cohen, S. M. (Nat. Rev. Mater., 2016)

(untitled) - Smaldone, R. A.; Forgan, R. S.; Furukawa, H.; Gassensmith, J. J.; Slawin, A. M.; Yaghi, O. M.; Stoddart, J. F. (Angew. Chem., Int. Ed., 2010)

(untitled) - Campbell, M. G.; Liu, S. F.; Swager, T. M.; Dincă, M. (J. Am. Chem. Soc., 2015)

(untitled) - Orellana-Tavra, C.; Baxter, E. F.; Tian, T.; Bennett, T. D.; Slater, N. K. H.; Cheetham, A. K.; Fairen-Jimenez, D. (Chem. Commun., 2015)

(untitled) - Lee, J.; Farha, O. K.; Roberts, J.; Scheidt, K. A.; Nguyen, S. T.; Hupp, J. T. (Chem. Soc. Rev., 2009)

(untitled) - Ayoub, G.; Islamoglu, T.; Goswami, S.; Friščić, T.; Farha, O. K. (ACS Appl. Mater. Interfaces, 2019)

(untitled) - Howarth, A. J.; Liu, Y.; Li, P.; Li, Z.; Wang, T. C.; Hupp, J. T.; Farha, O. K. (Nat. Rev. Mater., 2016)

(untitled) - Feng, D.; Gu, Z.-Y.; Li, J.-R.; Jiang, H.-L.; Wei, Z.; Zhou, H.-C. (Angew. Chem., Int. Ed., 2012)

(untitled) - Liu, Y.; Howarth, A. J.; Vermeulen, N. A.; Moon, S.-Y.; Hupp, J. T.; Farha, O. K. (Coord. Chem. Rev., 2017)

(untitled) - Buru, C. T.; Majewski, M. B.; Howarth, A. J.; Lavroff, R. H.; Kung, C.-W.; Peters, A. W.; Goswami, S.; Farha, O. K. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Gil-San-Millan, R.; López-Maya, E.; Hall, M.; Padial, N. M.; Peterson, G. W.; DeCoste, J. B.; Rodríguez-Albelo, L. M.; Oltra, J. E.; Barea, E.; Navarro, J. A. R. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - DeCoste, J. B.; Peterson, G. W. (Chem. Rev., 2014)

(untitled) - Lv, X.-L.; Yuan, S.; Xie, L.-H.; Darke, H. F.; Chen, Y.; He, T.; Dong, C.; Wang, B.; Zhang, Y.-Z.; Li, J.-R.; Zhou, H.-C. (J. Am. Chem. Soc., 2019)

(untitled) - Liu, Y.; Buru, C. T.; Howarth, A. J.; Mahle, J. J.; Buchanan, J. H.; DeCoste, J. B.; Hupp, J. T.; Farha, O. K. (J. Mater. Chem. A, 2016)

(untitled) - Bobbitt, N. S.; Mendonca, M. L.; Howarth, A. J.; Islamoglu, T.; Hupp, J. T.; Farha, O. K.; Snurr, R. Q. (Chem. Soc. Rev., 2017)

(untitled) - Zhang, X.; Huang, Z.; Ferrandon, M.; Yang, D.; Robison, L.; Li, P.; Wang, T. C.; Delferro, M.; Farha, O. K. (Nat. Catal., 2018)